Altered Brain Glucose Metabolism Assessed by 18F-FDG PET Imaging Is Associated with the Cognitive Impairment of CADASIL. (1st October 2019) - Su, Jingjing; Huang, Qi; Ren, Shuhua; Xie, Fang; Zhai, Yu; Guan, Yihui; Liu, Jianren; Hua, Fengchun
Abstract: Recurrent stroke and cognitive impairment are the primary features of patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). The cognitive deficits in these patients are known to be correlated with structural brain changes, such as white matter lesions and lacunae, and resting-state functional connectivity in brain networks. However, the associations between changes in brain glucose metabolism based on 18 F-2-fluoro-2-deoxy-D-glucose ( 18 F-FDG) positron emission tomography (PET) imaging and cognitive scores in CADASIL patients remain unclear. In the present study, 24 CADASIL patients and 24 matched healthy controls underwent 18 F-FDG PET imaging. Brain glucose metabolism was measured in all subjects and Pearson's correlation analyses were performed to evaluate relationships between abnormal glucose metabolism in various brain areas and cognitive scores. Compared to controls, CADASIL patients exhibited significantly lower metabolism in the right cerebellar posterior lobe, left cerebellar anterior lobe, bilateral thalamus and left limbic lobe. Additionally, hypermetabolism was observed in the left precentral and postcentral gyri. Importantly, glucose metabolism in the left limbic lobe was positively associated with cognitive scores on the Mini-Mental State Examination (MMSE). Furthermore, glucose metabolism in the left precentral gyri was negatively correlated with cognitive scores on the Montreal Cognitive Assessment (MoCA). The present findings provide strong support for the presence of altered brain glucose metabolism in CADASIL patients as well as the associations between abnormal metabolism and cognitive scales in this population. The present findings suggest that patterns of brain glucose metabolism may become useful markers of cognitive impairment in CADASIL patients. Highlights: Lower metabolism in the cerebellum, thalamus and limbic lobe in CADASIL. Hypermetabolism in the left precentral and postcentral gyri in CADASIL. Significant associations between abnormal metabolism and cognitive scales in CADASIL.